Pharmacogenetic testing to predict antipsychotic-induced weight gain: a systematic review. (August 2011) - Risselada, Arne J; Mulder, Hans; Heerdink, Eibert R; Egberts, Toine CG
Weight gain is an important side effect of antipsychotic drugs. Since the high interindividual difference in weight gain suggests that genetic factors play a role in this weight gain, studies have tried to identify these factors. Most of these studies were carried out in the past few years and focussed largely on receptor polymorphisms, although some tried to explain the variation in weight gain by differences in pharmacokinetics. Unfortunately, the results of these association studies are often conflicting, which makes it hard to apply this genetic knowledge in daily clinical practice. This article summarizes the findings of these association studies and focuses on differences in study methodology in an attempt to explain why study results could have been conflicting. Furthermore, the feasibility of genetic testing in today's clinical practice is discussed, using a model that consists of four components; analytical validity, clinical validity, clinical utility and ethical, legal and social issues.